The crystal structure of 2-(2-fluorophenyl)naphtho[2,1-d]thiazole, C17H10FNS - Zhu Xiaoming; Jin Hongsheng (Zeitschrift für Kristallographie - New Crystal Structures)
C17H10FNS, monoclinic, P21/n (no. 14), a = 6.1859(2) Å, b = 10.7071(2) Å, c = 19.4475(4) Å, β = 95.794(2)°, V = 1281.49(5) Å3, Z = 4, R gt(F) = 0.0476, wR ref(F 2) = 0.1333, T = 296 (2) K.